Mechanisms of tamoxifen resistance: insight from long non-coding RNAs - Yan, Yuxin; Zhang, Jian (Frontiers in Oncology, 2024)
Breast cancer(BC) is the second most prevalent tumor in the world and one of the most lethal tumors in women. Patients with estrogen receptor-positive breast cancer can obtain significant advantages from endocrine therapies including tamoxifen, aromatase inhibitors, and others. However, the development of primary or acquired drug resistance ultimately leads to discontinuation of treatment with adverse consequences for breast cancer patients, and the underlying mechanisms have not been fully elucidated. Long non-coding RNAs (lncRNAs) play pivotal roles in orchestrating fundamental biochemical and cellular processes. They exert regulatory control over various processes including epigenetics, gene transcription, post-transcriptional modifications, and translation. Additionally, they influence key biological events like cell cycle progression, cell differentiation, and development. For the past few years, the relationship between lncRNAs and endocrine resistance has gained increasing attention, leading to a surge in related studies. LncRNAs mediate tamoxifen resistance in cancer by utilizing a variety of molecular mechanisms, including enhanced estrogen receptor (ER) signaling, inhibition of apoptosis, autophagy, exosome-mediated transfer, epigenetic alterations, epithelial-to-mesenchymal transition, and acting as competitive endogenous RNAs(ceRNAs). In this comprehensive review, we systematically summarize the critical role and intricate molecular mechanisms by which lncRNAs influence the development of tamoxifen resistance in breast cancer. Furthermore, we propose the potential clinical significance of lncRNAs as innovative therapeutic targets and prognostic biomarkers for breast cancer.